Acceptability and facilitators of and barriers to point‐of‐care HIV testing in a homeless‐focused service in Gloucestershire: a qualitative evaluation. Issue 3 (24th October 2021) - Corker, Elizabeth; Lorencatto, Fabiana; Anderson, Niall; Gobin, Maya; Scott, Sarah; Michie, Susan; Angel, Georgina
Abstract: Objectives: Late HIV diagnosis increases the risks of onward transmission, morbidity and mortality. Rapid point‐of‐care testing (POCT) reaches people who have never been tested and people living with HIV who are undiagnosed. This study explored the acceptability and feasibility of HIV POCT from the perspectives of service providers and users. Methods: A pilot study introduced HIV POCT to one service in Gloucestershire, England. Eleven semi‐structured interviews with service users and a focus group with three service providers were conducted. The Theoretical Framework of Acceptability and the Theoretical Domains Framework were used to design the topic guide and analysis. Results: Acceptability of HIV POCT was high. Seven facilitators were identified (e.g. understanding the test purpose and process), alongside two potential barriers, one relevant to service providers and users (anxiety) and the other to service users (stigma). Conclusions: To maximize the benefits of implementation of HIV POCT, health care providers require appropriate training and supervision to offer and administer POCT.